COLLECTION ORGANIZATION: REFLECTIONS ON SPORTIVE HISTORY, MEMORIES AND CULTURES (Fiep Bulletin - online, 2014)
This work is a study that aims to reflect on the process of how modern sportive memories is built, taking as reference Infamous sportive memory collection (AMEI) of the Physical Education College from the Federal University of Pelotas (ESEF/UFPEL). This collection organization was started in 2002 when it is donated about 10 thousand volumes to the university ESEF/UFPEL from the Instituto Histórico e Geográfico de Pelotas (Historical and Geographical institute of Pelotas). Afterwards, in 2005, it was started the collection organizational work with the official support of the Ministry of Sports (by the Net Cedes action) and the Ministry of Culture (by the Chibarro Mix Culture). During the preservation and socialization of the collection - cleaning, registering, cataloguing, and digitalizing it - we faced a local, regional, national and international sportive memory composed by a great oral, imagetic and written sources.
Keywords: Memory; Sport; Culture